INDIGENOUS COMMUNITY EMPOWERMENT POLICY FOR STRENGTHENING NATIONAL MARITIME DEFENSE - Puri Maharani, Andina Elok; Leksono, Avivah Firisqi; Shinta Putri, Dyah Erie (Cepalo, 2024)
Community participation is mandatory as stipulated in Law Number 1 of 2014 which amends Law Number 27 of 2007 concerning the Management of Coastal Areas and Small Islands. Challenges still occur in the implementation of this regulation, particularly regarding the suboptimal involvement of coastal Indigenous communities in managing their territories. This research examines how coastal Indigenous communities contribute to national maritime defense and how Government policies can empower them to enhance national defense. Utilizing a normative juridical approach, the research reviews and analyzes existing literature. The findings indicate that empowering coastal Indigenous communities plays a crucial role in preserving marine ecosystems, monitoring coastal areas, and identifying maritime threats, thereby strengthening national defense. Effective empowerment requires synergy between the central and regional Governments in policy formulation, ensuring community involvement. The novelty of this research lies in its proposal to formally integrate coastal Indigenous communities as a central element in national maritime defense, thus enhancing Indonesia’s maritime resilience.